Penggunaan Metode Jarimatika melalui Media Game Quizizz untuk Meningkatkan Hasil Belajar Siswa Materi Perkalian di Kelas IV SDN.152/III Batang Sangir - Mega Pustika; Mulza Rois (Kilau Publishing, 2024)
The aim of this research is to find out whether the use of the Jarimatika method and the Quizizz game media in multiplication material can improve student learning outcomes. This type of research is Classroom Action Research (PTK). This research was carried out over two cycles. There are four phases to each cycle: planning, action, observation, and reflection. In each research cycle, a test method is used to collect data through observation and documentation. The results showed that only 33.33% of students completed the pre-cycle cycle, increasing to 50% in cycle 1 and in cycle II it increased again to 83.33%. This shows that the mathematics strategy assisted by the Quizizz game media has succeeded in improving student learning outcomes.